Correction: Improvement of cytocompatibility of 3D-printing resins for endothelial cell adhesion. Issue 109 (10th November 2016) - Lu, Zuyan; Jiang, Xia; Zuo, Xiao; Feng, Li
Abstract : Correction for 'Improvement of cytocompatibility of 3D-printing resins for endothelial cell adhesion' by Zuyan Lu et al., RSC Adv., 2016, 6, 102381–102388.